Boosting the power conversion efficiency of perovskite solar cells to 17.7% with an indolo[3, 2-b]carbazole dopant-free hole transporting material by improving its spatial configuration. Issue 24 (5th June 2019) - Cai, Bin; Yang, Xichuan; Jiang, Xiaoqing; Yu, Ze; Hagfeldt, Anders; Sun, Licheng
Abstract : Three-step synthesis and facile modification of an indolo[3, 2- b ]carbazole based dopant-free hole transporting material resulted in a power conversion efficiency of 17.7% in perovskite solar cells. Abstract : The development of facilely synthesized, dopant-free hole-transporting materials (HTMs) with high efficiency is of great significance for the potential application of perovskite solar cells (PSCs). Herein, we report two novel indolo[3, 2- b ]carbazole (ICZ) based small molecules obtained via a three-step reaction in a high yield without using expensive catalysts, namely C201 and C202, and further apply them as dopant-free HTMs in PSCs. Compared with C201, C202 contains two additional biphenylamino groups to improve its spatial configuration. It is found that the interplay between the molecular geometry and the aggregation behavior can exert a great influence on the film formation property and thus on the device performance. Strikingly, the champion devices employing C202 as the HTM deliver a much higher PCE of up to 17.7%, which is substantially higher than that of devices containing C201 (8.7%) under 100 mW cm −2 illumination (AM 1.5G). It is revealed that the C202 capping layer exhibits a more homogeneous and uniform surface morphology as compared to that of C201, which effectively reduces the charge recombination losses and facilitates charge extraction, leading to a much-enhanced photovoltaic performance. This is the first example of ICZ core-based small molecules as dopant-free HTMs in PSCs. Moreover, the PSCs containing C202 as the HTM also exhibited good long-term stability under ambient conditions (40% RH) as compared to devices with doped spiro-OMeTAD, due largely to the hydrophobic nature of C202 which prevented moisture from destroying the perovskite film. This work offers a new avenue for developing cost-effective and stable HTMs for PSCs and other optoelectronic devices.